QUANTITATIVE STUDIES ON DOWNY MILDEW Peronospora destructor AFFECTING ON GROWTH AND ONION SEED PRODUCTION IN UPPER EUPHRATES AREA - & et al., Al- Maadhedi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted during the seasons 2009 and 2010 using local Red onion cultivar in order to determine the plant densities (the best distance between the plants) and the timing control (the best time to spray fungicide) for the purpose of reducing Downy Mildew (DM) incidence and severity, to improve the quality of vegetative growth and flowering in order to achieve high seed yielding. The distances 10, 15, 20, 25, and 30 cm between the plants were used, and six dates of spraying the fungicide (Redomil MZ 72 WP) was attempted; after one month of planting, after 60 days of planting, twice spraying one after one month followed with another after a month, when reveal 50% of flowering racemes, and after 100% of the plants was flowering, as well as the comparison treatment without spraying. This study revealed that the plant density 25 cm between the plants was the best among the other plant densities, where given the highest % of flowering, number of blossoms racemes plant-1, % of floral fertilization, reduction in % of infection with DM, so was obtained the highest production of seeds, reaching; 63.75%, 2.99 racemes/plant, 64.27%, 14.86 %, and 408.48 kg.ha-1., respectively. Results also showed that treating the plants two times with the fungicide, the first after one month followed with another after a month and using the plant density 25 cm between the plants was achieved a significant increase on a number of tubular blade, %of flowering, number of blossoms raceme.plant-1, %of floral fertilization, reduction in %of infection with DM, so was obtained the highest production of seeds, reaching ; 9.92 Blades.plant-1, 64.44 %, 3.17, 80.41 %, 4.38 %, and 423.63 kg.ha-1., respectively.